International Interim Awards Enforcement under the Indonesian Arbitration Law and UNCITRAL Model Law - Labib Wajdi, Muhammad; Adolf, Huala; Amalia, Prita (Journal of Law, Politic and Humanities, 2024)
The Indonesian umbrella regulation for arbitration, Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, is silent regarding the enforcement of interim awards which creates uncertainty of law. This is in contrast to the arbitration-friendly regulations stemming from the UNCITRAL Model Law that are found in Asia’s leading arbitral seats such as Hong Kong and Singapore. Presently, there is a growing demand for seats to adopt a mechanism for enforcing interim awards in international arbitration, as the absence of such enforcement undermines the efficacy of an effective justice system in transnational trade. Therefore, an analysis is needed to review the enforcement of interim awards under the Indonesian arbitration law and how it compares to the UNCITRAL Model Law, the Hong Kong Arbitration Ordinance, and the Singapore International Arbitration Act. Through the research, we found that there is a discrepancy both in the existence of an enforcement mechanism for interim awards and in the consistency between the law and practice in Indonesia, Hong Kong, and Singapore. In order for Indonesia to enhance its appeal as an arbitral seat, the uncertainty regarding the enforcement of interim awards must be remedied.